The experiences of CSSD and OR staff in relation to missing surgical instruments at a public hospital, Eastern Region, Saudi Arabia - Simmons, Annalene (Stellenbosch : Stellenbosch University, 2021)
Thesis (MNur)--Stellenbosch University, 2021.